Influenza vaccination in immunocompromised populations: Strategies to improve immunogenicity. Issue 1 (15th March 2021) - Caldera, Freddy; Mercer, Monica; Samson, Sandrine I.; Pitt, Jonathan M.; Hayney, Mary S.
Abstract: Immunocompromised individuals are at high risk of severe illness and complications from influenza infection. For this reason, immunization using inactivated influenza vaccines is recommended for transplant patients, individuals receiving immunosuppressant treatments, and other persons with immunodeficiency. However, these immunocompromised populations are more likely to have lower and non-protective responses to annual vaccination with a standard influenza vaccine. Here, we review strategies aimed to improve the immunogenicity of influenza vaccines in immunocompromised populations. The different strategies employed have included adjuvanted vaccines, high-dose vaccines, booster doses, intradermal vaccination, and temporary discontinuation of immunosuppressant treatment regimens. High-dose trivalent, inactivated, split-virus influenza vaccine (IIV3-HD) is so far one of the leading strategies for improving vaccine responses in HIV patients, transplant patients, and persons receiving immunosuppressant therapies for inflammatory diseases. Several studies in these populations have shown stronger humoral responses with IIV3-HD than existing standard-dose trivalent vaccine, and comparable safety. Accordingly, some scientific societies have stated that high-dose influenza vaccine could be a preferred option for immunocompromised patients. However, larger randomized controlled studies are needed to validate relative immunogenicity and safety of IIV3-HD and other enhanced vaccines and vaccination strategies in immunocompromised individuals.